PENDAMPINGAN IMPLEMENTASI KURIKULUM MERDEKA DI UPT SD NEGERI 49 GRESIK. - Ismail Marzuki; Iqnatia Alfiansyah (Bajang Institute, 2024)
In 2023 the Ministry of Education, Culture, Research, Technology, and Higher Education has lounching the Independent Curriculum Implementation independently (IKM). Related to this, there are many new things that must be mastered by teachers and principals in implementing the new curriculum. This assistance focuses on helping teachers and principals so that the implementation of the IKM can run smoothly. The assistance is specifically to help schools create unit operational curricula Education Unit (KOSP), helps teachers compile learning objectives and learning objectives flow, helps teachers compile teaching modules, carry out differentiated learning, and learning assessment. The results of this assistance show that there are positive changes in teachers in insight and enthusiasm to implement the independent curriculum independently in schools.